Environment flows: moving from concepts to application, a case study from India - Bharati, Luna; Smakhtin, Vladimir U.; Eriyagama, Nishadi; Anand, B.K. (2009)
Water allocation rules are put in place to ensure that various parties receive a portion of developed water supplies. Allocation of river water to cities, industries and agriculture has been a common practice but now there is an increasing recognition of the need to also allocate water for environmental purposes. Furthermore, it is now recognized that such environmental water demands need to be considered explicitly alongside those of other users early on, at the planning and design stages of water resource development projects. This paper describes a desktop hydrology-based environmental flow assessment method developed at the International Water Management Institute and it's applicability in river basin management. A case study from India is presented where the feasibility of a proposed water transfer scheme from the Godawari River at Polavaram to the Krishna river is analyzed. The characteristic feature of the study is the simulation of the impact of various feasible cropping patterns on water demands as well as the explicit inclusion, of environmental water requirements in the simulations. The WEAP (Water Evaluation and Planning) model was applied to simulate water supply versus demand under the current water use and under water use anticipated after the construction of the Polavaram reservoir and link canal. Results suggest that the proposed Polavaram reservoir and canal system will reduce the seasonal pressure on water for the command area of the project. However, this may result in increased water deficits from December to June in the Lower Godavari Delta, downstream of the Polavaram reservoir. The importance of explicit accounting for monthly variability in description of water supply and demands in the conditions of monsoon-driven climate of the region is advocated. Similarly, the need to ensure environmental flows should also be considered in the context of seasonal variability, as it is mostly in the dry months that water allocation problems become critical. Such detailed scenario analysis can help to create awareness of potential future problems, inform water management practices and suggest management alternatives.